Common-cavity ytterbium/Raman random distributed feedback fiber laser. (4th May 2017) - Wu, Han; Wang, Zinan; He, Qiheng; Sun, Wei; Rao, Yunjiang
Abstract: In this letter, a common-cavity random distributed feedback fiber laser which can generate both 1064 nm ytterbium-doped random lasing and 1115 nm ytterbium-Raman random lasing is proposed and experimentally demonstrated for the first time. The common cavity is based on the combination of the double-cladding ytterbium-doped fiber and the standard single mode fiber (SMF); a 1064 nm high-reflectivity fiber Bragg grating and the fiber flat-end are connected to the signal port of the pump combiner as the point reflectors. The generated 1064 nm random lasing can serve as the Raman pump in the SMF, thus 1115 nm random lasing could be stimulated with the hybrid ytterbium-Raman gain. The feedback for 1115 nm random lasing is the combination of flat-end fiber and random Rayleigh feedback. By controlling the value of flat-end fiber's reflectivity to 0.002, stable 1.91 W of 1064 nm ytterbium-doped random lasing and 3.72 W of 1115 nm ytterbium-Raman random lasing are generated successively. This work could provide a simple and cost-effective way to generate high-power random lasing.